Perbaikan Kondisi Kerja Melalui SHIP Approach Ergonomic Meningkatkan Kualitas Kesehatan dan Produktivitas Pada Pekerja Peyulingan Minyak Cengkeh : Improving Working Conditions Through the SHIP Ergonomic Approach Increases Health Quality and Productivity of Clove Oil Refinery Workers - Saputra, I Kadek Dwi Arta; Ardiyanti, Ni Putu (Universitas Mohammad Husni Thamrin, 2025)
Clove leaf oil distillation workers face working conditions with high environmental temperatures, non-ergonomic working postures, and a lack of understanding of occupational safety principles. These conditions potentially increase the risk of health problems and decrease productivity if no improvements are made. This study aims to improve workers’ health and productivity through the SHIP Approach Ergonomic intervention. The intervention included education on proper working posture, short rest periods, banana consumption, and stretching exercises before and after work. Environmental improvements were carried out by installing ventilation and providing 250 ml of drinking water every working hour. The research design used was Quasi-Experiment with a pre- and post-test without control design. The target population was all clove leaf oil distillation workers in four central locations in Kayuputih Village, Banjar District, Buleleng Regency, with a sample of 28 workers. Data analysis employed parametric tests (α=0.05) for normally distributed data and non-parametric tests for non-normally distributed data. The results showed that the SHIP Approach Ergonomic intervention improved workers’ health and productivity, indicated by a 22.28% reduction in musculoskeletal disorder (MSDs) complaints, a 7.74% decrease in blood pressure, and a 2.30% reduction in body temperature after work..